Recurrent genuine empty follicle syndrome: a rare case report - Mahapatro, Akshaya Kumar; Shankar, Kundavi; Varma, Thankam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Failure to aspirate oocytes from follicles after Controlled ovarian stimulation with apparently normal growing follicles with normal steroidgenesis after meticulous follicular aspiration is called Empty follicular syndrome (EFS). EFS are mainly two types, Genuine EFS & False EFS. Here we report a case of 24 yrs female presenting with primary subfertility with normal ovarian reserve, husband having normal semen analysis, planned for In vitro fertilization for failed Intra uterine insemination (IUI) & underwent two cycles of oocytes retrieval after controlled ovarian stimulation. We couldn’t retrieve any oocytes in spite of adequate serum βhCG level in both the cycles. Karyotyping of the patient was normal (46 XX). In this patient we were not able to find out any cause for recurrent genuine empty follicle syndrome. So we advised the couple to opt for oocyte donation program.